Microbiological evaluation on raw materials and food contact surfaces of ‘keropok lekor’ premises in Kuala Nerus, Terengganu and their prevalence of antibiotic resistant bacteria - Lani M.N.; Peng T.A.; Suhaili Z.; Hassan Z. (Malaysian Society of Applied Biology, 2024)
Indexed by Scopus